Genome-wide analysis of copy number variations identifies PARK2 as a candidate gene for autism spectrum disorder. Issue 1 (December 2016) - Yin, Chia-Lin; Chen, Hsin-I; Li, Ling-Hui; Chien, Yi-Ling; Liao, Hsiao-Mei; Chou, Miao; Chou, Wen-Jiun; Tsai, Wen-Che; Chiu, Yen-Nan; Wu, Yu-Yu; Lo, Chen-Zen; Wu, Jer-Yuarn; et al.
Abstract Background Autism spectrum disorder (ASD) is an early-onset neurodevelopmental disorder with complex genetic underpinning in its etiology. Copy number variations (CNVs) as one of the genetic factors associated with ASD have been addressed in recent genome-wide association studies (GWAS). However, the significance of CNV has not been well investigated in non-Caucasian ASD population. Methods To identify the pathogenic CNVs responsible for ASD in Han Chinese, we performed a segment-based GWAS of CNV in 335 ASD cases and 1093 healthy controls using Affymetrix single nucleotide polymorphism (SNP) array by focusing on case-specific CNVs.PARK2 was one of the important genes with several case-specific regions overlapped on it. The findings were validated in the initial screen sample set and replicated in another sample set by real-time quantitative PCR (qPCR). Results A total of six CNVs at 6q26 that spanned different exons ofPARK2 were identified. ThePARK2 expression level was down-regulated at exon-dependent manner in cases with either deletion or duplication. The result revealed that the gene function might be disrupted by exonic deletion and duplication. We also observed that the ASD case with exonic duplication demonstrated a more severe interference ofPARK2 expression and the clinical feature than the ones with deletion at the exons 2–4 of thePARK2 gene. Conclusions Our finding provides evidence to support that CNVs affectingPARK2 function might contribute to genetic etiology of a proportion of cases with ASD. The intriguing results of this work warrant further study on characterizing the functional impact of various exonic CNVs on thePARK2 gene. Trial registration ClinicalTrials.govNCT00494754